Investigation of Electron Contamination on Flattened and Unflattened Varian Clinac iX 6X and 15X Photon Beam Based on Monte Carlo Simulation - F. Haryanto; M. F. Rhani; C. Anam; S. Yani (Atom Indonesia, 2022)
The aim of this study was to characterize electron contamination of a flattened (FF) and an unflattened (FFF) Varian Clinac iX 6X and 15X photon beams using Monte Carlo (MC) simulation. EGSnrc MC technique was used to model the flattened and unflattened head and simulate dose distribution of 6X and 15X of FF and FFF photon beam in water phantom. The materials and geometrical data of FF linac were provided by Tan Tock Seng Hospital (TTSH) Singapore. The FFF linac was modeled by removing the flattening filter component in the FF linac. Phase space files were scored after flattening filter and in the phantom surface. The phsp files were analyzed to characterize the particles produced by the linac head using BEAMDP. The contaminants contribute around 1 % and 2 % in the phsp1 for flattened and unflattened beams, respectively. The photons are scattered in small-angle in the range of 0 – 4o. The contaminant electron contributes up to one hundredth compared to the photons. The increase of field area affects the increase in contaminants and penumbra width due to the increasing number of particle scattered out of the field area. The unflattened beam affects the increase in the number of electron contamination and surface dose. The penumbra width of the flattened beams was smaller than the unflattened beams for the same field size and energy.